Development of graphical display for helicopter simulation - Koh, Kok Liang. (2010)
The development of rotary aircraft has progressed by leap and bounds since the early 20th century. Progressive improvements of aircraft development have also extended the use of such aircraft from a passenger carrier to that of autonomous operation; an UAV or unmanned aerial vehicle. The use of computer software to develop an aircraft has also heralded in a new era whereby designers can easily test and simulate their proposed ideas on their workstations before implementation. This project will study the development of a helicopter within a computer simulated environment using off the shelf tool and open source software. The core development stages would be the graphical representation of the helicopter in the simulation as well as the actual physics representation which will propel the simulated aircraft to flight.